Gambaran Pengetahuan Dan Sikap Ibu Hamil Tentang Triple Eliminasi Di Puskesmas Purwodadi II - Vera Rahmawati; Runjati Runjati; Erna Widyastuti (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
The screening results at the Purwodadi II Health Center indicated an increase in cases of HIV, Syphilis, and Hepatitis B in 2021-2022; specifically, HIV increased from 0 to 1 case, Syphilis from 0 to 2 cases, and Hepatitis B from 6 to 10 cases. In order to reduce the incidence rate, the government conducted screenings during the integrated ANC, which included a Triple Elimination examination consisting of HIV, Syphilis, and Hepatitis B tests. The purpose of the study was to determine the characteristics, knowledge, and attitudes of pregnant women about Triple Elimination at Purwodadi II Health Center. This research was conducted in the Purwodadi II Health Center area using a descriptive research design. The study population consisted of pregnant women who had not undergone the Triple Elimination examination at the Purwodadi II Health Center in 2023. The sampling technique involved accidental sampling of 79 respondents. The results showed that most pregnant women in the reproductive age category were healthy, had secondary education, and mostly were housewives and multiparous, with limited knowledge and negative attitudes towards Triple Elimination. Therefore, the health workers need to provide education about Triple Elimination to enhance the knowledge and positive attitudes of pregnant women in the future.